Study guides

Q: Y equals -x plus 12x-y equals 5 solve by substitution?

Write your answer...

Submit

Related questions

(2,3)

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You'd need another equation to sub in

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

-2

How do you solve 4y plus x equals 8

-2 plus 5 equals +3

2x-3y=13

Not enough information to solve

It is not possible to do so because the question contains one equation (5x + y = 1) and one expression (3x + 2y + 2). An expression cannot be solved.

The GCF is 4.

Substitution property.

2x + 2y = 44x + y = 1There are many methods you can use to solve this system of equations (graphing, elimination, substitution, matrices)...but no matter what method you use, you should get x = -1/3 and y = 7/3.

3x2 - 2y2 = 9x2 + 4y2 - 12xy (subtract 3x2 and add 2y2 to both sides) 0 = 9x2 -3x2 + 4y2 + 2y2 - 12xy 0 = 6x2 + 6y2 - 12xy (divide by 6 to both sides) 0 = x2 + y2 - 12xy or x2 - 2xy + y2 = 0 (x - y)(x - y) = 0 x - y = 0 x = y

(x + 5y)(x + 7y)

To solve this one, subtract 50 from 180 and you'll have your answer.

Px equals -0.6 plus 60x-1500

many solutions

5

If you mean x+2y = -2 and 3x+4y = 6 then by solving the simultaneous equations by substitution x = 10 and y = -6

x = -2 and y = 1

Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7

a= -0.8

(3,3)

A is 14